Pengaruh Pengembangan Sumber Daya Manusia Terhadap Kinerja Karyawan Bank Syariah Mandiri Kantor Cabang Medan - Kris Setiawan (Jurnal Niaga & Bisnis (e-journal), 2015)
The purpose of this research is to know the possibility of the influence of human resources development to employees’ performance, to know if there any significant influence and to know how big the influence between human resources development and employees` performance in Bank Syariah Mandiri Medan branch. This research method used associative research method with quantitative data analysis that search the relation between variable X and variable Y. Variable X is human resources development and variable Y is employees` performance. Sample of this research is all of the employees` in Bank Syariah Mandiri office Medan branch. The sample took using total sampling technique with total 35 people. The data collected then analyzed using quantitative data analysis technique. Based on the result of research and continue with analyze collected data using correlation product moment formula, then the result is there is the significant relation and positive in middle degree between human resources development to employees` performance about 0,427 and value of sig (2-tailed)  is 0,010<0,05.  With the value of the influence of human resources development to performance employee’s is about 18,2%. Keywords : Human Resources,Employees Performance